Legal Analysis of Electronic Signatures in Nigeria - Olusoga-Tinubi, Hannah (African Journal of Stability and Development (AJSD), 2018)
From 3100 B.C. when the scribe Gar Ama made his markings on a Sumerian clay tablet, through the years succeeding 1677 when the Statute of Fraud was passed into law by the British Parliament, till this present moment in 2018 , signatures were and continue to serve as a form of communication. Signatures may not only communicate the signatory’s approval and adoption of the contents of a document but may also be able to authenticate the contents of a document as originating from the signatory. Though signatures are traditionally handwritten, the giant leaps experienced in the 21st century in the field of information and communication technology have ushered in the era of the increasing use of signatures which are electronically written. The use of electronic signatures is made even more popular by stakeholders in commerce and industry who rely on technological innovations especially as it has to do with communication to facilitate commercial transactions. Considering that laws are not made in isolation but made to respond to the needs of an ever-evolving society, several legal systems across the globe are adjusting to regulate this new and non-negligible, aspect of contract and commercial law This paper examines the place and significance of electronic signatures in the Nigerian legal system by analysing how well-adjusted the current state of laws is to the recognition and regulation of the use of electronic signatures in Nigerian commercial transactions